Wave 2 Data Management Issues - LSAC Discussion Paper No. 5 - Misson, S (My University, 2007)
The data management policy and procedures for Wave 2 of Growing Up in Australia - the Longitudinal Study of Australian Children (LSAC) are discussed in this paper. The paper covers key data management issues, including: variable naming conventions; file structure; treatment of household composition data; data confidentialisation; data imputation; and weighting of data. It also reviews current policy and procedure, as implemented following the release of Wave 1 data, and further discusses some potential revisions and additions to these in light of the forthcoming release of Wave 2 data, which will be the first major release of a longitudinal dataset from the study.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology